Determinan Faktor Yang Mempengaruhi Kinerja UMKM di Kota Semarang - Riva Meutia Febriana Safitri; Achmad Badjuri (STEKOM PRESS, 2022)
This study aims to find empirical evidence about the effect of accounting knowledge, owner's perception, entrepreneurship orientation, market orientation, performance of micro, small and medium enterprises. This research is a quantitative research using primary data obtained from questionnaires that have been distributed and measured using a likert scale. The population in this study were all owners of micro, small and medium enterprises in North Semarang sub-district with a total of 1683 businesses. The sampling method used in this research is probability sampling. Based on probability sampling method, obtained 95 respondents. Test results from the instrument in this study is valid and reliable. Data analysis techniques used is multiple linear regression analysis using SPSS version 21. The results in this study indicate that accounting knowledge and owner's perception affect the performance of micro, small and medium enterprises, while entrepreneurship orientation and market orientation have no effect on the performance of micro, small and medium enterprises.